Perbandingan Efektivitas Latihan Daya Tahan Aerobik dan Latihan Resistensi Terhadap Penurunan Gula Darah Harian Pada Lansia Di Puskesmas Puter Kota Bandung - Ramania, Nia Sri; Alviana, Irana Mery; Rawildati, Awalia Dinis; Rachmatullah, Charis; Hartianto, Naufal Dzaki; Muda, Iskandar (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2024)
Diabetes Mellitus (DM) is a chronic condition that occurs when there is an increase in glucose levels in the blood because the body cannot produce insulin or use insulin effectively. Insulin is an important hormone produced in the body's pancreatic gland, which transports glucose from the bloodstream into the body's cells where the glucose is converted into energy. This study uses a comparative study with experimental method to find out the comparison results of the treatment given to samples from aerobic exercise intervention treatment with resistance exercise, The first group will do Aerobic Endurance Exercise by walking for 20 minutes. While the second group will do Resistance Exercise by doing strength training or resistance training for 20 minutes, rest time is 15 seconds and the movement is done as many as 2 sets and 10 repetitions. Subject characteristics based on average age (61.58 ± 6.50), body weight (71.86 ± 9.76), body height (157.27 ± 8.99), and BMI of elderly people suffering from diabetes mellitus falls into the obese category with a value of (27.71 ± 4.23). The value of aerobic before exercise is (26.41 ± 33.67) after exercise it decrease (11.74 ± 10.28), resistance exercise before exercise is (31.74 ± 54.10) after exercise it decrease (9.33 ± 23.46). In this study it can be concluded that aerobic endurance and resistance exercise can reduce the increase in blood sugar in the elderly, but when compared to the two exercises, resistance exercise suppresses the increase in blood sugar more, of course with the appropriate intensity.